Assessment of the validity of the Resilience and Strain Questionnaire in Caregivers of People with Dementia (ResQ-Care-Dem): a cross-sectional survey study - Bernhard Holle; Kerstin Köhler; Iris Blotenberg; Jochen René Thyrian; Melanie Boekholt; Alexandra Wuttke (BMJ Open)
Objectives The aim of the present study was to examine the reliability and validity (structural and convergent) of the Resilience and Strain Questionnaire in Caregivers of People with Dementia (ResQ-Care-Dem).Design Cross-sectional survey study.Setting Online survey in Germany.Participants The ResQ-Care-Dem was completed by 243 informal caregivers of people with dementia (Mage=59.7 years, SD=10.9, 84.8% female).Methods The ResQ-Care-Dem consists of four scales: two resilience scales (psychological aspects and social aspects of resilience) and two burden scales (interpersonal burden and general burden). The reliability of the two resilience and two burden scales was assessed using Cronbach’s alpha as a measure of internal consistency. Structural validity was examined using a principal axis factor analysis. Convergent validity was assessed by Pearson’s correlations with the Zarit Burden Interview (ZBI-7), the Caregiver Self-Efficacy Scale (CES-8) and the Gain in Alzheimer Care Instrument (GAIN).Results The ResQ-Care-Dem scales’ internal consistencies ranged between 0.65 and 0.81. The factorial structure could partly be confirmed, with the items of the four scales primarily loading on four factors. The burden scales demonstrated high and positive correlations with the score for caregiver burden (ZBI-7, r=0.51 – 0.55) and small to high, negative correlations with the scores for caregiver self-efficacy (CES-8, r=–0.52 –0.56) and gains from caregiving (GAIN, r=−0.21 −0.22), supporting construct validity of the scales. The resilience scales showed small to high positive correlations with the scores for caregiver self-efficacy (CES-8, r=0.50 – 0.57) and gains from caregiving (GAIN, r=0.27 – 0.50), as well as moderate negative correlations with the caregiver burden score (ZBI-7, r=−0.45 −0.50), providing evidence for the scales’ construct validity.Conclusions The reliability and structural validity of the ResQ-Care-Dem were partially confirmed. Evidence supporting its convergent validity suggests that the questionnaire has potential as a tool for assessing caregiver burden and resilience factors among informal caregivers of people with dementia. While these findings indicate potential practical applicability, future studies should investigate its performance in real-world settings and assess changes over time (eg, responsiveness) in longitudinal studies.